2011
DOI: 10.1016/j.alcohol.2011.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Acute ethanol exposure prevents PMA-mediated augmentation of N-methyl-d-aspartate receptor function in primary cultured cerebellar granule cells

Abstract: Many intracellular proteins and signaling cascades contribute to the ethanol sensitivity of native N-methyl-d-aspartate receptors (NMDARs). One putative protein is the serine / threonine kinase, Protein kinase C (PKC). The purpose of this study was to assess if PKC modulates the ethanol sensitivity of native NMDARs expressed in primary cultured cerebellar granule cells (CGCs). With the whole-cell patch-clamp technique, we assessed if ethanol inhibition of NMDA-induced currents (INMDA) (100 μM NMDA plus 10 μM g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Reneau et al . () demonstrated that ethanol (1–100 mM) inhibited PKCα activity in vitro by up to 40%, although we and others found less inhibition of PKCα activity by ethanol (Slater et al, ; Rex et al, ; Llorente et al, ). However, such in vitro studies using purified PKC are likely to be hindered by the absence of cofactors that are required for ethanol inhibition of the enzyme and also do not examine the initial translocation of PKC from the cytoplasm to the plasma membrane.…”
Section: Discussionmentioning
confidence: 49%
“…Reneau et al . () demonstrated that ethanol (1–100 mM) inhibited PKCα activity in vitro by up to 40%, although we and others found less inhibition of PKCα activity by ethanol (Slater et al, ; Rex et al, ; Llorente et al, ). However, such in vitro studies using purified PKC are likely to be hindered by the absence of cofactors that are required for ethanol inhibition of the enzyme and also do not examine the initial translocation of PKC from the cytoplasm to the plasma membrane.…”
Section: Discussionmentioning
confidence: 49%
“…Different groups have reported different results when examining the effects of ethanol on PKCa activity. Slater et al (1997) and Reneau et al (2011) reported a modest inhibition of PKCa by ethanol, whereas Rex et al (2008) found no effect of ethanol on PKCa. We therefore sought to determine ourselves whether …”
Section: Resultsmentioning
confidence: 95%
“…This is in part because the effects of ethanol are PKC isoform specific and also vary with the location of the enzyme, how it is activated, the substrate used, and the cofactors present (Stubbs and Slater, 1999;Newton and Ron 2007). Slater et al (1997), using lipid vesicles, observed that ethanol inhibited PKCa by 20% at 50 mM and that the effect was dependent upon the presence of DAG; and Reneau et al (2011), using purified PKCa alone (i.e., not in lipid vesicles), observed a 20% inhibition of PKCa by 10 mM ethanol. In contrast, Rex et al (2008) reported that at 100 mM ethanol did not inhibit lipid-activated PKCa but did inhibit PKCg and PKCd.…”
Section: Discussionmentioning
confidence: 99%
“…Acute EtOH can inhibit activation of PKC by interfering with translocation to the plasma membrane (Slater et al., ; Steiner et al., ). The effect of EtOH on PKC differs by subtype of PKC, as PKCα (Reneau et al., ; Slater et al., ), PKCγ (Harris et al., ; Rex et al., ), and PKCδ (Rex et al., ) have been reported to be inhibited by EtOH, but other isoforms are resistant to EtOH inhibition, like PKCβ1 and PKCε, for example (Rex et al., ). Other laboratories have shown that EtOH can enhance the activity of some PKC isoforms, such as PKCε (Messing et al., ; Satoh et al., ).…”
Section: Discussionmentioning
confidence: 99%